Policies to implement smart learning in higher education - Sousa, M. J.; Sousa, M. (Proceedings of the European Conference on e-Learning, ECEL 2019, 2019)
This article aims to analyze the smart technologies and contexts that can potentiate digital learning in Higher Education. First of all, the research will focus on the definition of the concepts of digital learning, smart learning technologies, and smart learning contexts. Digital learning is all learning activity that uses, in a significant way, information, and communication technologies. It is interactive learning in which the learning content is available online. To operationalize this research, it was applied a Delphi methodology, in order to discuss with a set of experts the environments where smart learning and which technologies could potentiate the learning process in Higher Education (HEI) Contexts. The lines of analysis of this investigation were oriented according to the following research questions: What types of digital learning can be used to potentiate the learning process of students of higher education? What are the leading smart technologies used in the digital learning process? Which are the smart contexts that can potentiate the learning process? The main findings of the learning process will be the identification of smart learning types, technologies, and contexts. The articles will intent to define some lines of orientation for the definition of public policies to promote the learning process in Higher Education.